2023
DOI: 10.3390/mi14071459
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrically Nanostructured 2D Janus Films Obtained from Pickering Emulsions Polymerized in a Langmuir–Blodgett Trough

Abstract: Low-dimensional structures, such as two-dimensional (2D) Janus films, can be useful in studying fundamental interactions or in applications at the nanoscale. In this work, we report the fabrication of 2D polymer Janus films consisting of one smooth and another nanostructured facet on which silica nanoparticles (NPs) are self-assembled in a compact monolayer shield. The 2D films are made from Pickering emulsions of monomers in water, stabilized by NPs, which are spread over the surface of the water in a Langmui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…As we will see next, the SiO 2 -PEI NPs exclusively occupy the monomer/water interface. A similar phenomenon was also observed in the case of silica nanoparticles bearing different functional groups, such as glycidyl, and was observed for other particles bearing surface functional groups with a higher component of the dispersive surface energy [26]. The monomer droplet/water interfacial tension is stabilized by the presence of the nanoparticles.…”
Section: Synthesis Of the Langmuir-blodgett 2d P(t-ba)/sio 2 -Pei Np ...supporting
confidence: 78%
See 2 more Smart Citations
“…As we will see next, the SiO 2 -PEI NPs exclusively occupy the monomer/water interface. A similar phenomenon was also observed in the case of silica nanoparticles bearing different functional groups, such as glycidyl, and was observed for other particles bearing surface functional groups with a higher component of the dispersive surface energy [26]. The monomer droplet/water interfacial tension is stabilized by the presence of the nanoparticles.…”
Section: Synthesis Of the Langmuir-blodgett 2d P(t-ba)/sio 2 -Pei Np ...supporting
confidence: 78%
“…The process of forming Janus 2D P(t-BA)/SiO 2 -PEI NP films from the Pickering emulsions in an L-B trough is similar to the one we have previously reported [26]. Briefly, the Pickering emulsion droplets (colloidosomes) were added onto the surface of a Langmuir-Blodgett trough with a spatula.…”
Section: Synthesis Of the Langmuir-blodgett 2d P(t-ba)/sio 2 -Pei Np ...mentioning
confidence: 88%
See 1 more Smart Citation
“…The method utilizes oil-in-water (o/w) Pickering emulsions, emulsions that are stabilized by silica nanoparticles, and the dispersed phase is a water-immiscible vinyl-bearing monomer. As a side note, other groups utilize the same technology for producing microporous polymer monoliths [10] and asymmetrically structured Janus membranes [26]. The silica nanoparticles utilized in the current work are 500 ± 10 nm diameter silica nanoparticles modified with glycidyl functional groups on the surface (see Figure 1A), which have been previously shown to produce preferentially o/w emulsions [27].…”
Section: Preparation Via Pemptech and Characterization Of Polymer Mic...mentioning
confidence: 96%
“…The implications of nanostructuring in the waterwetting of the polymer microspheres are significant. We have previously demonstrated that for a hydrophobic polymer whose typical water contact angles are around 80 • , due to the nanostructuring from a self-assembled monolayer of NP-Gly on the surface of the polymer, the wettability increases significantly, lowering the water contact angles to values below 60 • characteristic for a hydrophilic surface [26]. This improvement in water wettability due to nanostructuring has significant implications for the extraction of metal ions from aqueous solutions by these polymer microspheres.…”
Section: Preparation Via Pemptech and Characterization Of Polymer Mic...mentioning
confidence: 99%